2019
DOI: 10.1007/s11060-019-03102-5
|View full text |Cite
|
Sign up to set email alerts
|

EGFR amplification and classical subtype are associated with a poor response to bevacizumab in recurrent glioblastoma

Abstract: Purpose The highly vascular malignant brain tumor glioblastoma (GBM) appears to be an ideal target for anti-angiogenic therapy; however, clinical trials to date suggest the VEGF antibody bevacizumab affects only progression-free survival. Here we analyze a group of patients with GBM who received bevacizumab treatment at recurrence and are stratified according to tumor molecular and genomic profile (TCGA classification), with the goal of identifying molecular predictors of the response to bevacizumab. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 29 publications
0
16
2
2
Order By: Relevance
“…It is well established that there are several subtypes of glioblastoma based on their gene expression and DNA mutation characteristics and treatment responses (pro-neural, neural, mesenchymal and classical) 50,51 . EGFR amplification and mutations are more often found in glioblastomas in the classical sub-type 52,53 . Our current results indicate that treatment of TMZ and irradiation selects for a population of cells that have reduced EGFR.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that there are several subtypes of glioblastoma based on their gene expression and DNA mutation characteristics and treatment responses (pro-neural, neural, mesenchymal and classical) 50,51 . EGFR amplification and mutations are more often found in glioblastomas in the classical sub-type 52,53 . Our current results indicate that treatment of TMZ and irradiation selects for a population of cells that have reduced EGFR.…”
Section: Discussionmentioning
confidence: 99%
“…Manneh Kopp et al 21 reported no significant correlation between the clinical outcome in patients with recurrent GBM treated with Bev and histopathological parameters such as the Ki‐67 labeling index, various molecules including c‐Met, HIF‐1, and VEGFA, and neuroradiological parameters. Hovinga et al 22 recently analyzed time to progression in GBM patients treated with Bev and reported that epidermal growth factor receptor amplification and the classical subtype are associated with a poor response to Bev in recurrent GBM. Here, we demonstrated that the P/C ratio of CD44 expression in GBM was significantly correlated with responsiveness to Bev for the treatment of recurrent GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Bevacizumab has been approved for treatment of recurrent HGG and improves the steroid-free interval and progression-free survival, albeit without an impact on overall survival [ 5 ]. EGFR amplification is associated with poor response to bevacizumab in recurrent GBM [ 6 ]. As most scGBMs show EGFR amplification, the role of bevacizumab is unclear.…”
Section: Discussionmentioning
confidence: 99%